Business under occupation : how do Palestinian industrial companies on the West Bank and Gaza become successful? - Larsson, Peder; Lengquist, Eva (Linkoping Linkoping University, Department of management Engineering. Division of Industrial Marketing, 2011)
Abstract: This master thesis explores how Palestinian manufacturing companies on the West Bank become successful. The study was executed on the West Bank during two months in the fall of 2011 and was funded by the Swedish International Development Cooperation Agency (SIDA). It is interesting to explore how the companies become successful since the West Bank is occupied by the state of Israel. The occupation has imposed curfews, closures, checkpoints, political uncertainties and high costs of production inputs on Palestinian companies. Combined with the strict import and export regulations and procedures derived from the Oslo process, it makes running a business in this environment very difficult. The study was performed as a multiple case study on eight successful companies and the data was analysed according to an analysis model that was developed before the field study. The definition of a successful company is a company that survived the second intifada and that today has more than 30 employees. The Palestinian context carries many risks, which requires a willingness to take risks and a good risk management. Doing this well can put a company ahead of competitors. Access to capital is vital and is explaining how some of the companies have managed to survive during hard times. The local market in the Occupied Palestinian Territories is very small, and Israel is the largest export market for Palestinian industrial companies. Export to third countries together with product diversification seem to be important in order to expand the market and also to decrease the economic dependence on Israel. One of the most important explanations of why Palestinian companies become successful is the connections and relations of its leaders. They all seem to have powerful connections both within the Occupied Palestinian Territories, within its administration the Palestinian Authority and with Israeli agents and friends. These connections can facilitate import, export and movement of goods and people. This aspect, which gives companies different tools to deal with the restrictions and uncertainties, is skewing the competition between companies. To succeed in the Palestinian context it is important to have strong and patient leadersm who are committed to build a great company. Feeling that they are contributing to the creation of a Palestinian state is important in order to be able to cope with the hard conditions. Understanding the importance of recruiting the right people and taking good care of them when employed is another important step towards success. This also includes continuous trainings and taking pride in developing the skills of the workforce. How good as the companies ever become at the above propositions, the occupation is still suffocating the Palestinian economy and making the Palestinian companies less competitive compared to international companies. All the interviewed companies thought that they would perform much better without the occupation and stated the occupation as the biggest threat to further development of their business. The problem for the companies is not a lack of management, the occupation is, which is crucial to consider when working with business support and development in the Occupied Palestinian Territories.
Page numbers do not appear on the printed copy. For page numbers see attached PDF file.
Includes bibliographical references
Keywords: Business enterprises; BUSINESS ENTERPRISES; ISRAELI OCCUPATION OF PALESTINE 1948-; ISRAEL; POLITICS; INDUSTRIAL ENTERPRISES; GAZA STRIP; WEST BANK